Additional Leave as the Determinant of Retirement Timing—Retaining Older Workers in Norway - Hermansen, Åsmund (Nordic Journal of Working Life Studies, 2015)
Faced with a rapidly aging labor force, increasing the labor supply of older workers has become an important goal for European countries. Offering additional leave to older workers with the option of withdrawing a contractual pension (contractual early retirement pension AFP) has become a widespread retention measure in Norwegian companies. Thus far, no studies documenting the effects of individual retention measures on early retirement behavior have been published. The aim of this article is to examine whether offering additional leave impacts the relative risk of withdrawal of a contractual pension. The analysis uses a difference-in-differences approach and examines whether offering additional leave to counteract early retirement impacts the retirement decisions of 61- and 62-year-olds within the next two years of their employment, controlling for a range of different individual and company characteristics. This is achieved by comparing changes and differences in the individual relative risk of retiring early on the contractual pension (AFP scheme) in the period 2001–2010 among older workers in companies with and without the retention measure. The analysis shows an overall average increase in the relative risk of a 61- or 62-year-old worker retiring on the contractual pension between 2001 and 2010; however, among older workers employed in companies offering additional leave there has been a decrease in the relative risk. The effect of additional leave is evident both before and after controlling for the selected individual and company characteristics. Thus, the analysis shows that offering additional leave as a retention measure reduces the individual relative risk of withdrawing a contractual pension (AFP) in the next two years of employment among older workers between the age of 61 and 62 years.